(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2013)
Two-phase local heat transfer coefficient and flow pattern in 4.5 cm inner length of glass square test section downwardly pipe inclination angles of 5o, 10o, and 15o were investigated experimentally. Two superficial velocities for each air and water were used 0.164 m/s, 0.411 m/s and 1.1506 m/s, 1.4815m/s respectively. Local heat transfer coefficient was calculated from the temperature recorded by using eight thermocouples type K positioned along the test section. It was found that the heat transfer coefficient of air-water flow increase with increasing flow rate of water, air, and inclination angle. In addition a high speed camera was used in order to obtain images sequence of the flow under different selected conditions. The flow regimes, which are stratified, intermittent, and annular flow are observed and recorded by high speed camera. At 5o inclination angle and low air-water superficial velocity stratified flow observed, transition from stratified to intermittent flow and annular flow occurs at increasing the inclination angle and air-water superficial velocity. Correlations on average Nusselt number were obtained for three inclination angle 5o, 10o, and 15o.